2004
DOI: 10.1073/pnas.0404843101
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of complex dynamics in a simple model of signaling networks

Abstract: Various physical, social, and biological systems generate complex fluctuations with correlations across multiple time scales. In physiologic systems, these long-range correlations are altered with disease and aging. Such correlated fluctuations in living systems have been attributed to the interaction of multiple control systems; however, the mechanisms underlying this behavior remain unknown. Here, we show that a number of distinct classes of dynamical behaviors, including correlated fluctuations characterize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 31 publications
3
73
0
Order By: Relevance
“…Investigations elucidating the link between dynamics and topology in complex networks are needed to ultimately understand the evolutionary building principles of biological networks. The incorporation of noise or disorder in such systems is a natural step towards realistic models [8,9]. Qualitatively speaking, there are two possible ways of introducing disorder: On the level of signals and on the level of architecture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations elucidating the link between dynamics and topology in complex networks are needed to ultimately understand the evolutionary building principles of biological networks. The incorporation of noise or disorder in such systems is a natural step towards realistic models [8,9]. Qualitatively speaking, there are two possible ways of introducing disorder: On the level of signals and on the level of architecture.…”
mentioning
confidence: 99%
“…In order to definitely classify the pattern evolution with a single observable one could use the entropy measure proposed by Wolfram in [6], where all possible words, including non-constant l-words, are accounted for. Instead, we will apply the (statistically less demanding) detrended fluctuation analysis (DFA) to reveal the complexity of the binary network dynamics, as applied in [9].…”
mentioning
confidence: 99%
“…They also consider the number of inputs and outputs for components. Boolean networks can analyze data that describe the state of a single variable and the average state of all other neighbors [104][105][106]. They do not require knowledge about concentrations and the kinetic parameters of components.…”
Section: From Signaling Pathways To a Network Signaling Via Proteomicmentioning
confidence: 99%
“…Moreover, given that different nodes may have now different degrees, Watts used a simple majority rule 4 as a transition function, a rule that cannot classify density in a regular CA. In [27] it was shown that such high-performance GAN can be obtained automatically and easily with a simple evolutionary algorithm, starting from either regular or completely random graphs.…”
Section: Collective Tasks On Gan: Density and Synchronizationmentioning
confidence: 99%
“…Due to their novelty, and in spite of their potential interest, there have been comparatively few studies of the computational and dynamical properties of automata networks. Notable exceptions are [26,30,24,27,28,19] which mainly deal with extensions of classical CA, and a few recent articles on Boolean automata networks [3,4,21,13].…”
mentioning
confidence: 99%